Innovation and Recycling—Drivers of Circular Economy in EU - Platon, Victor; Pavelescu, Florin Marius; Antonescu, Daniela; Frone, Simona; Constantinescu, Andreea; Popa, Florina (Frontiers in Environmental Science, 2022)
In our days, growing attention is paid to explain the influence of innovation on recycling. While many studies on this subject have been carried out, there is still a lack of investigation on measuring the effect of innovation on recycling. This paper is dedicated to measuring the intensity of the innovation influence on the recycling within EU member states. In addition, the influence of other variable, as membership of Euro area, on the progress in recycling is high-lighted. The main method of investigation is the panel regression model, applied within several steps: determining the analyzed series stationarity using unit root test, developing a regression panel model for 28 EU countries, applying specific statistical tests (Housman) to differentiate between models. The proposed econometric model has shown that the influence of the innovation on recycling is moderate and not instantaneous; a two years lag is present between the in-novation inception and its measurable effect on recycling. The article has several originality aspects: it took into account criteria that are not discussed very often; it has developed a model that brings quantitative features to describe the influence of innovation on recycling.